PARADIGMA PENDIDIKAN ISLAM MULTIDIMENSIONAL: Konsep dan Implikasinya dalam PAI di Sekolah/Madrasah - Rahmi Anekasari (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2015)
Indonesian Islamic education is experiencing a never ending crisis leadingto loss of its philosophical foundation and vagueness of its objectives.Consequently, Islamic education results in a number of incompleteness in awide range of its facets; in technology, global interconnection, and even inmorality. A multidimensional Islamic education serves as a paradigm ofeducation that employs a multidimensional approach integrating religion,philosophy and science. Islam views knowledge as a means to save human’ssoul and to reach one’s happiness here and hereafter. It is an educationfocusing on an integration of robbaniyah (divinity), insaniyah (humanity),and alamiyah (nature) to realise the duty of Islam as rahmatan lil ‘alaminand to maintain the balance between rationality, morality, andspirituality